Expanding Access: Opportunity to Strengthen Food Security during the Covid-19 Pandemic (A Study on the Poor in Tamansari District, Tasikmalaya City) - Nasution, Fatimah Zahra; Surgawati, Iis (Jurnal Akuntansi, Manajemen dan Ekonomi, 2023)
This study aims to estimate food security maps, measuring opportunities for physical access, economic access, and social access to food both partially and jointly in strengthening food security and to test the independence between food security and poverty during the Covid-19 pandemic in poor households in Tamansari District, Tasikmalaya City. The research method used is the explanatory method, while the data analysis method uses proportion estimation and regression analysis and the Chi-Square test. The results showed that during the Covid-19 pandemic, it was estimated that there were around 1.34% to 10.66% of poor people in Tamansari District, Tasikmalaya City who were classified as "severe food insecure", 15.63% to 32.37% classified as "prone to food" or “moderate level of food insecurity”, 53.54% to 72.46% classified as “slightly food insecure” and 2.00% to 12.00% classified as “food safety”. Another finding is that partially physical access and economic access have a very large opportunity, namely 97.1% and 99.2%, while social access is 46.7% in strengthening food security during the Covid-19 pandemic for poor communities in Tamansari District Tasikmalaya City. Together, the opportunities for physical access, economic access and social access in strengthening food security during the Covid-19 pandemic are even close to 100%. This study did not show any relationship between food security and poverty.